Potential chemoprotective effects of active ingredients in Salvia miltiorrhiza on doxorubicin-induced cardiotoxicity: a systematic review of in vitro and in vivo studies - Wang, Qingqing; Li, Jiaxian; Chu, Xuelei; Jiang, Xiaochen; Zhang, Chuanlong; Liu, Fudong; Zhang, Xiyuan; Li, Yi; Shen, Qian; Pang, Bo (Frontiers in Cardiovascular Medicine, 2023)
Background Recently, attention has been paid to the protective properties of active ingredients in Salvia miltiorrhiza (AISM) against organ toxicity induced by chemotherapy drugs. Purpose of the present systematic review is to evaluate the chemoprotective effects and mechanisms of AISM on in vitro and in vivo models of doxorubicin-induced cardiotoxicity (DIC). Methods According to the PRISMA guideline, the current systematic review was conducted in the Web of Science, PubMed, Embase, and the Cochrane Library to collect all relevant in vitro and in vivo studies on “the role of AISM on DIC” published up until May 2023. The SYRCLE's tool was used to identify potential risk of bias. Results Twenty-two eligible articles were included in this systematic review. Eleven types of active ingredients in Salvia miltiorrhiza were used for DIC, which have the following effects: improvement of physical signs and biochemical indicators, reduction of cardiac function damage caused by DIC, protection of heart tissue structure, enhancement of myocardial cell viability, prevention of cardiomyocyte apoptosis, increase of the chemosensitivity of cancer cells to Doxorubicin, etc. The cardioprotective mechanism of AISM involves inhibiting apoptosis, attenuating oxidative stress, suppressing endoplasmic reticulum (ER) stress, decreasing inflammation, improving mitochondrial structure and function, affecting cellular autophagy and calcium homeostasis. The quality scores of included studies ranged from 4 to 7 points (a total of 10 points), according to SYRCLE's risk of bias tool. Conclusion This systematic review demonstrated that AISM have chemoprotective effects on DIC in vivo and in vitro models through several main mechanisms such as anti-apoptosis, antioxidant effects, anti-ER stress, and anti-inflammatory.